Experimental and theoretical study of the vibrational spectra of paraphenylenediamine transition metal (II) complexes - Akalın, Elif; AKYÜZ, SEVİM (Elsevier, 2001)
The effect of coordination of p-phenylenediamine molecule (PPD) to a transition metal has been investigated by making use of the normal coordinate analysis. The reliable force field of coordinated PPD have been determined by refinement of the free PPD in order to fit the experimental wavenumbers of transition metal (II) PPD complexes. Additionally, CdI2(PPD) and MnCl2(PPD) complexes have been prepared and their vibrational assignment is provided based on this calculation.
Keywords: Normal coordinate analysis; Paraphenylenediamine; Diaminobenzene; Complexes; IR spectrum; Force field